(untitled) (ENTHYMEMA, 2023)
This article investigates Primo Levi’s representations of the origin of life, particularly considering his essays and science-fiction short stories. After introducing the two main sources of inspiration that Levi refers to when writing narratives on this subject, classical and biblical mythologies and Darwinian evolutionary theory, the article offers a close reading of two short stories, “I sintetici” and “Disfilassi”, that depict a moment of ‘second genesis’ set in the near future. This process is seen by Levi from an ecological perspective in relation to the environmental risks that human technology and overpopulation pose to our planet. Following the analysis of the writer’s essays about recent chemical and biological theories on how life originated on Earth, the last paragraph focuses on the tangencies between Levi’s investigation of the origin of life and his reflections on the source of literary creativity, summed up by the short story “Carbonio”.